To generate greater economic benefits from visiting ships - Li, Tianyang (2018)
In order for Singapore to generate more economic benefits from visiting ships, past research papers, journals and reports used to focus on mainly two areas. One is for the Port of Singapore to become more attractive in terms of efficiency, functionality and lower cost so that more ships will come. The other is to provide more value-adding activities to the existing pool of visiting ships both in port and on shore. While recommendations proposed by these past research are feasible and valuable, they share a common trait — that is being too conservative. Technological breakthroughs and advancements are happening at a speed faster than ever. New opportunity presents us with ways to provide brand new categories of services to the maritime industry. These new services when implemented will improve efficiency of operations, adding value to visiting ships but at the same time, lowering the total operational cost. This project aims to examine the feasibility for application of these emerging technologies, especially on the application of the blockchain technology, in Singapore’s maritime industry. Therefore bolder and quicker move is required for Singapore to maintain its leading status and position in the maritime industry.